Impact of dairy trainings on productivity of herd, generation of income and employment - KHODE, NARENDRA; SINGH, B P; CHANDER, MAHESH; BARDHAN, D; VERMA, MED RAM; PAUL, A K (The Indian Journal of Animal Sciences, 2025)
The current study was conducted in Maharashtra to ascertain the impact of dairy farming trainings organized by selected three Krishi Vigyan Kendras on selected economically important parameters. Propensity score matching method was used to avoid selection bias and build a statistical comparison group of non-trainees comparable to trainees. The study revealed that there was no significant difference among trainees and non-trainees related to possession of dairy herd. However, study has shown that milk productivity, annual net income and annual employment generation among trainee and non-trainee dairy farmers were significantly different and comparatively higher among trainees than non-trainees, which indicates positive impact of training imparted by selected Krishi Vigyan Kendras in Maharashtra. Study further revealed that proportion of trainees who were deriving higher economic benefits from dairy farming in terms of productivity and income was quiet less. Hence, it is suggested that training organizing institutes should intensively plan more trainings of long duration ensuring larger and wider participation of population with follow up and post-training information support.